Nanocrystalline diamond surfaces for adhesion and growth of primary neurons, conflicting results and rational explanation - Ojovan, Silviya M.; McDonald, Mathew; Rabieh, Noha; Shmuel, Nava; Erez, Hadas; Nesladek, Milos; Spira, Micha E. (Frontiers in Neuroengineering, 2014)
Using a variety of proliferating cell types, it was shown that the surface of nanocrystalline-diamond (NCD) provides a permissive substrate for cell adhesion and development without the need of complex chemical functionalization prior to cell seeding. In an extensive series of experiments we found that, unlike proliferating cells, post-mitotic primary neurons do not adhere to bare NCD surfaces when cultured in defined medium. These observations raise questions on the potential use of bare NCD as an interfacing layer for neuronal devices. Nevertheless, we also found that classical chemical functionalization methods render the "hostile" bare NCD surfaces with adhesive properties that match those of classically functionalized substrates used extensively in biomedical research and applications. Based on the results, we propose a mechanism that accounts for the conflicting results; which on one hand claim that un-functionalized NCD provides a permissive substrate for cell adhesion and growth, while other reports demonstrate the opposite.